In vitro antifungal activity of various elicitors and binders against Alternaria solani - Meena, Bhanu Raj; Chittora, Deepali; Yadav, Jyoti; Meena, Sanjeev; Kumar, Suresh; Jain, Tripta; Sharma, Kanika (Journal of Postharvest Technology, 2022)
In the present study, in vitro antifungal activity of various elicitors like ground nut oil cake, mustard oil cake, cotton oil cake, sesame oil cake, coconut oil  cake and neem oil cake and binders like cow dung, guar gum and gum acacia were used with the aim to study on antifungal activity. Plant  products/extracts have been observed to be successful over traditional fungicides and microbial biocontrol agents. Acacia gum has long been used in  everyday applications and in traditional medicine. Cow dung also well-known as cow pad, is a constituent having crude protein, cellulose, hemicellulose  and minerals. It is proficient organic manure employed to enhance plant yield in fields. 20gm elicitors and binders were dissolved in 100 ml of autoclaved  water for 24 h. The mixture was then filtered and used for antifungal activity. Among the all Elicitors and all binders best optimum activity was observed  for neem oil cake and cow dung i.e. 60.32% and 36.36 % respectively against Alternaria solani. Results suggested that best elicitor i.e. neem oil cake  and binder cow dung cab be used to develop the plant extract based bio-formulation for effective control of early blight of potato in an eco- friendly  manner. These elicitors and binders improve fertility of the soil in which plants or crops are planted. Thus, use of these components cut the additional  cost of adding extra nutrients to soil. Neem cakes and cow dung can also get better the organic constituents of the soil by providing plenty of micro and  macro nutrients.
Keywords: Bio-formulation; elicitors; binders; oil cakes; cow dung